2021
DOI: 10.33503/journey.v4i1.1257
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECTIVENESS OF SMALL GROUP DISCUSSION IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT AT X GRADE IN SMAN 1 WOLOWAE

Abstract: The present study aims at exams the effectiveness of small group discusssion in teaching reading comprehension of narrative text of the tenth -grade students of SMA NEGERI 1 WOLOWAE. Teaching reading comprehension is recommended in Senior High School because reading comprehension is very important. In competence based on curriculum, students are understanding to comprehending the conten of the text. The research is carried out through quantitative research with an experimental method because the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The result showed that the Small Group Discussion method increased students' descriptive text writing skills, as shown by post-test scores that were better than pre-test findings. Accordance with Putra's finding, Usu and Adi (2021) carried out a research about the effectivity of using small group discussion in teaching reading comprehension of narrative text. According to Usu and Adi (2021), employing Small Group Discussion as a teaching strategy may significantly improve students' reading ability.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The result showed that the Small Group Discussion method increased students' descriptive text writing skills, as shown by post-test scores that were better than pre-test findings. Accordance with Putra's finding, Usu and Adi (2021) carried out a research about the effectivity of using small group discussion in teaching reading comprehension of narrative text. According to Usu and Adi (2021), employing Small Group Discussion as a teaching strategy may significantly improve students' reading ability.…”
Section: Introductionmentioning
confidence: 84%
“…Accordance with Putra's finding, Usu and Adi (2021) carried out a research about the effectivity of using small group discussion in teaching reading comprehension of narrative text. According to Usu and Adi (2021), employing Small Group Discussion as a teaching strategy may significantly improve students' reading ability. They suggested English teachers to use this method in the teaching and learning process.…”
Section: Introductionmentioning
confidence: 84%
“…The understanding obtained is an active thinking process of students. According to Usu & Adi, (2021), reading comprehension is a person capability to be capable process, adsorb the significance in the text. Therefore, by improving this capability, one can understand what the researcher expects when they read a text.…”
Section: Concept Of Reading Comprehensionmentioning
confidence: 99%
“…By reading people are required to find ideas in a text, not just for reading aloud. Usu & Adi (2021) state that the main purpose of reading activities not only allow students to understand fictional texts as entertainment because one of the benefits of reading fiction books is to sharpen the brain to explore. The fiction text is like a short story or novel.…”
Section: Introductionmentioning
confidence: 99%